2020
DOI: 10.1016/j.jcv.2020.104682
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of VitaPCR SARS-CoV-2 to the emergency diagnosis of COVID-19

Abstract: Background With the persistent COVID-19 pandemic, there is an urgent need to use rapid and reliable diagnostic tools for highly urgent cases. Antigen tests are disappointing with their lack of sensitivity. Among molecular tools allowing a diagnosis in less than an hour, only one, the Cepheid Xpert Xpress SARS-CoV-2 assay, has exhibited a good sensitivity. However, we are also facing a global shortage of reagents and kits. Thus, it is imperative to evaluate other point-of-care molecular tests. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 10 publications
2
30
1
Order By: Relevance
“…Our observations confirm the previous analytical evaluation of the VitaPCR™ platform for SARS-CoV-2 RNA molecular detection by Fournier and colleagues, 16 | 4355 late phase of the infection typically associated with a low viral load.…”
Section: Discussionsupporting
confidence: 90%
“…Our observations confirm the previous analytical evaluation of the VitaPCR™ platform for SARS-CoV-2 RNA molecular detection by Fournier and colleagues, 16 | 4355 late phase of the infection typically associated with a low viral load.…”
Section: Discussionsupporting
confidence: 90%
“…All studies examined paired NP swabs tested with the Panbio and a PCR-based platform, with two of the four studies using the Allplex (Seegene, South Korea) [3,4]. One study [2] used the VitaPCR SARS-CoV-2 (Credo diagnostics, Singapore) that has limited data available on its performance, which may explain why 7 samples were Panbio positive but VitaPCR SARS-CoV-2 negative [10]. Gremmels et al performed testing on the Panbio up to 2 h from collection, which may account for the lower sensitivity detected (72.6%) [3].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 One study used the VitaPCR SARS-CoV-2 (Credo diagnostics, Singapore) that has limited data available on its performance, which may potentially explain why 7 samples were Panbio positive but VitaPCR SARS-CoV-2 negative. 9 Gremmels et al performed testing on the Panbio up to 2 hours from collection, which may account for the lower sensitivity detected (72.6%). 3 Of the studies that examined positivity rate based on symptom duration, one study found no difference in positivity rate with duration of symptom onset 3 , whereas another found higher sensitivity in individuals with symptom onset < 7 days (sensitivity 86.5%) compared to individuals with symptom onset ≥ 7 days (sensitivity 53.8%).…”
Section: Resultsmentioning
confidence: 99%
“…3,4 One study 2 used the VitaPCR SARS-CoV-2 (Credo diagnostics, Singapore) that has limited data available on its performance, which may potentially explain why 7 samples were Panbio positive but VitaPCR SARS-CoV-2 negative. 9 Gremmels et al . performed testing on the Panbio up to 2 hours from collection, which may account for the lower sensitivity detected (72.6%).…”
Section: Discussionmentioning
confidence: 99%